Efectividad de un programa para controlar la ansiedad y la emotividad frente al examen de Papanicolaou en mujeres de la Institución Prestadora de Servicios de Salud en la ciudad de Nauta 2020 - Freitas Perez, Leandro Ademir (2025)
Anxiety and emotionality were common reactions in women to the Pap smear, especially in settings with limited access to medical information. This led to postponement or abandonment of the exam. This situation compromises the early detection of cervical cancer, a disease preventable with timely diagnosis. In this regard, the general objective was: to determine the effectiveness of a psychoeducational program for controlling anxiety and emotionality in women who attended the Pap smear at IPRESS Nauta during 2020, taking into account that, in some cases, it leads to postponement or definitive abandonment of the exam, which entails personal and family risks that must be prevented and addressed. A methodology was developed: a quantitative, longitudinal study with a quasi-experimental design was designed. 60 women between the ages of 30 and 64 participated, divided into two groups: experimental (30 women) and control (30 women). Both groups were assessed before and after the intervention using validated questionnaires to measure anxiety and affectivity. The program was applied only to the experimental group. For statistical analysis the Student's "T" test was used for related and independent samples, the results: the results revealed that there were no significant differences between the groups at the beginning of the study, however, after the application of the program, the experimental group showed significant improvements in both anxiety and affectivity (P<0.05)., being affectivity, the experimental group that went from a normal-low average to a high normal level, while the control group did not show relevant changes, subsequently to that the anxiety group, being the experimental group maintained low levels post intervention, evidencing an improvement in emotional control, unlike the control group that varied significantly., the "T" test for paired and independent samples confirmed that the changes observed in the experimental group were statistically significant, while in the control group no substantial differences were recorded between the pre and post test. Finally, the conclusions were that the psychoeducational program was effective in reducing anxiety and strengthening emotional coping in women facing the Pap smear. This study supports its application to other similar populations as a preventive measure to increase adherence to this medical practice.